(untitled) (Nepal Journal of Epidemiology, 2014)
Abstracts of the Poster Presentations at the session on Communicable Diseases at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10149